PENGARUH IMPLEMENTASI KEBIJAKAN REFORMASI BIROKRASI TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH KABUPATEN MINAHASA TENGGARA - Tumiwa, Valen; Posumah, Jhonny Hanny; Kiyai, Burhanuddin (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : Governance of area can walk because of existence of support various resource factor capable to move organizational wheel of governance in order to attainment of target management of area autonomy, including in it is Earnings Of Genuiness Area. Problem of which in questioning in this research is how a far influence of Implementation Policy Of Reform Bureaucracy To Revenue Of Genuiness Area Sub-Province of Minahasa South-East".Method which used in this research is quantitative method. this Research Subyek is public servant of civil in On Duty Earnings Of Area Sub- Province of Minahasa South-East. Sampel Research taken by counted 39 people, consist of 23 people of PNS and the rest counted 16 people officer honorer.data collecting by using kuesioner Result of data analysis After calculated by using correlation analysis of product assisted moment with analysis of tools of program of Exel, hence obtained by correlation coefficient of Implementation Policy Of Reform Bureaucracy ( X) to Earnings Of Genuiness Area ( Y) is real and positive and correlation coefficient and also determinasi reside in at high category. Relate at pickings analyse data which have been elaborated by previous shares, hence it is can be pulled by some final conclusion as follows. 1. Implementation policy of bureaucracy reform represent one of the determinant revenue of area genuiness. 2. Result of statistical analysis indicate that between implementation policy of bureaucracy reform with revenue of area genuiness have relation of kontributif and have positive linear pattern . Relation both of variable very signifikan at level test 1%, whereas degree of determinant energy equal to 87,8%. Mounting and or down it revenue of Genuiness Area Sub-Province of Minahasa South-East equal to 87,8 % determined by Reform Bureaucracy factor. Keyword : Implementation Policy, Revenue Of Genuiness Area